2015
DOI: 10.1039/c5cp00802f
|View full text |Cite
|
Sign up to set email alerts
|

Activation and deformation of immobilized lipase on self-assembled monolayers with tailored wettability

Abstract: In this work, lipase from Candida rugosa (CRL) was immobilized on self-assembled monolayers (SAMs) with various wettabilities ranging from highly hydrophilic to highly hydrophobic by adsorption in order to clearly elucidate the interfacial activation character of lipases. The SAMs were made of 11-hydroxyundecane-1-thiol and 1-dodecanethiol. The adsorption behavior was monitored in situ by quartz crystal microbalance with dissipation (QCM-D), and the enzyme binding constants indicated a stronger affinity betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Therefore, the amide I band was used herein. A second derivative analysis to locate peaks due to secondary structural components was adopted [24,29]. After second derivative analysis of amide I (1600-1700 cm −1 ) bands, the second derivatives of the spectra are shown in Fig.…”
Section: Enzyme Structure and Kinetic Behavior Analysis Of Anl@m-zif-mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the amide I band was used herein. A second derivative analysis to locate peaks due to secondary structural components was adopted [24,29]. After second derivative analysis of amide I (1600-1700 cm −1 ) bands, the second derivatives of the spectra are shown in Fig.…”
Section: Enzyme Structure and Kinetic Behavior Analysis Of Anl@m-zif-mentioning
confidence: 99%
“…Considering the hydrophilic property of glycerol may result in the adsorption on the lipase, hydrophobic modification on the carrier of the immobilized lipase may lessen the adsorption of glycerol to a great extent. Despite of the fact that some researches observed the performance improvement of immobilized lipase by enhancing the hydrophobicity of supports mainly through influencing enzyme conformation [24][25][26], the influence on glycerol adsorption during biodiesel production has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…They achieved a fatty acid methyl ester (FAME) yield of 95.2% with 5:1 M ratio of methanol to oil and 4% Novozym 435 at 45°C for 10 h. The type of support influences the activity and operational stability of immobilized lipases. Numerous supports have been investigated, including macroporous and microporous polymers, silica sol-gel matrix or aerogels, ordered mesoporous silica, and other porous ceramics [13][14][15][16]. In recent years, mesoporous silica nanoparticles have received increasing attention in enzyme and protein immobilization because of their tunable and uniform pore system, high specific surface area, great compatibility, and low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(n-butylamino) 1.67 (allylamino) 0.33 phosphazene film had a water contact angle of 113.6 • , meaning a 30 • increase compared with that of poly(allylamino)phosphazene. In the previous work done by us, lipase was found to adsorb on the support easily with a water contact angle of 105.9 • , with a higher enzyme binding constant value, and the hydrophobic interaction can expose the catalytic site and produce even and regular protein deposition, which activate the lipase [16]. Thus we used poly(n-butylamino) 1 …”
Section: Effect Of Side Group Ratios On Polymer Hydrophilicitymentioning
confidence: 99%
“…Therefore, special emphasis has been put on immobilizing lipases onto hydrophobic support surfaces in recent years, which is based on the assumption that the active state of lipases can be stabilized by the hydrophobic interaction between the hydrophobic active center of lipases and the hydrophobic support [12][13][14][15]. In a previous study, we systematically studied the structural rearrangements, immobilization kinetics and protein aggregation of lipase from Candida rugosa absorbed on a wettability-tailored surface, and concluded that a support with proper hydrophobicity is of vital importance for obtaining a highly efficient immobilized lipase [16].…”
Section: Introductionmentioning
confidence: 99%